Sosialisasi Teknologi Digital Bagi Pelaku UMKM Kecamatan Sekupang - Permatasari, Ririt Dwiputri; Bora, M Ansyar; Hernando, Luki; Sondra Wijaya, I Made; Hazimah, Hazimah; Shilah, Nur; Fauzan, Haidil (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
The development of digital technology has transformed various aspects of life, including the micro, small, and medium enterprise (MSME) sector. In Sekupang District, the adoption of digital technology by MSME actors faces various challenges, particularly in understanding and accessing such technologies. The purpose of this digital technology outreach is to enhance the knowledge and skills of MSME actors in adopting technology, enabling them to compete in the digital era. This outreach activity includes a basic understanding of business software usage, digital marketing strategies, and the use of social media to expand market reach. The methods used include seminars, hands-on training, and Q&A sessions. The results of the outreach indicate an increase in MSME actors' understanding of the importance of digitalization and readiness to implement technology in daily business operations. This program is expected to increase the competitiveness of MSMEs in Sekupang District in facing the challenges of the digital economy.Keywords: outreach; digital technology; MSME; digitalization Abstrak: Perkembangan teknologi digital telah mengubah berbagai aspek kehidupan, termasuk sektor usaha mikro, kecil, dan menengah (UMKM). Di Kecamatan Sekupang, pemanfaatan teknologi digital oleh pelaku UMKM masih menghadapi berbagai tantangan, terutama dalam hal pemahaman dan akses terhadap teknologi tersebut. Sosialisasi teknologi digital bertujuan untuk meningkatkan pengetahuan dan keterampilan pelaku UMKM dalam mengadopsi teknologi, sehingga mampu bersaing di era digital. Kegiatan sosialisasi ini mencakup pemahaman dasar tentang penggunaan perangkat lunak bisnis, strategi pemasaran digital, serta pemanfaatan media sosial untuk memperluas jangkauan pasar. Metode yang digunakan meliputi seminar, pelatihan langsung, dan sesi tanya jawab. Hasil dari sosialisasi menunjukkan adanya peningkatan pemahaman pelaku UMKM mengenai pentingnya digitalisasi, serta kesiapan untuk mengimplementasikan teknologi dalam operasional bisnis sehari-hari. Program ini diharapkan dapat meningkatkan daya saing UMKM di Kecamatan Sekupang dalam menghadapi tantangan ekonomi digital.Kata kunci: sosialisasi; teknologi digital; UMKM; digitalisasi